Antibacterial Effects of Derivatives of Porphyrin, Naphthalene diimide, Aminophenol and Benzodioxane on Methicillin Resistant Staphylococcus aureus and Neuropathogenic Escherichia coli K1 - Siddiqui, Ruqaiyyah; Anwar, Ayaz; Ali, Salwa; Khan, Naveed A. (Anti-Infective Agents, 2020)
Background: Infectious diseases contribute to substantial mortality and morbidity worldwide despite advances in therapeutic intervention highlighting the need to identify drugs with antimicrobial properties. Methods: Here, we utilised several compounds from the following classes: porphyrin, naphthalene diimide, aminophenol derivatives, and benzodioxane, and evaluated their antibacterial activities. Bactericidal and bacteriostatic activity of these compounds were determined against methicillinresistant Staphylococcus aureus (MRSA) and Escherichia coli K1 with various concentrations of the drugs. Moreover, the ability of the bacteria to bind/associate to host cells was also ascertained in the absence and presence of aforementioned compounds. Results: The results revealed that porphyrin derivative (AYTHPP) had potent effects against MRSA, abolishing viability and blocking binding to the host cells. Importantly, novel AYTHPP exhibited powerful effects against MRSA even though it was not photoactivated. In contrast, other compounds, including naphthalene diimide, acetamol derivatives and benzodioxane, showed no inhibitory effects. Conclusion: The mechanism of action of porphyrin is likely through the production of reactive oxygen species causing oxidative stress, leading to apoptosis and/or necrosis via perturbations in the plasma membrane. Future studies will determine their in vivo efficacy together will associated molecular mode of action.
Keywords: chemotherapy